Estimating constant and time varying hedge ratios of Crude palm Oil futures (CPO) Contracts in Malaysia - Islam, Mohd Aminul (2016)
Futures contracts are one of the most common derivatives instruments used by the investors to hedge the risk exposures that may arise from adverse price movements. The effectiveness of futures contracts in managing risks is critical to the development of futures market. To design a better strategy with futures contracts for hedging the risk exposures, it is important that the hedger understand the optimal hedge ratio in order to be able to find the right number of futures contract for minimizing the risk. In this paper we estimated optimal hedge ratios of crude palm oil (CPO) futures contracts in Malaysia using daily settlement prices from January 4, 2010 to July 29, 2016. This comprises a total of 1615 observations. The hedge ratios are estimated by employing four competing econometric models namely: the standard Ordinary Least Square (OLS) regression, Error Correction Model (ECM), Generalized Autoregressive Conditional Heteroscedasticity (GARCH), and the bivariate GARCH (Diag-BEKK GARCH) model. The study found that the hedge ratios estimated by GARCH model are higher than those of other models for all futures contracts indicating that this model performs better in designing hedging strategy. The nearest futures contract (next one month contract) appears to be better in hedging than the far futures contracts (next two and three month contracts). The empirical finding suggests that the investor can use CPO futures contract particularly the nearest futures contract as an effective instrument to minimize the risk.